Hemispheric functional segregation facilitates target detection during sustained visuospatial attention. Issue 15 (13th June 2022) - DiNuzzo, Mauro; Mascali, Daniele; Bussu, Giorgia; Moraschi, Marta; Guidi, Maria; Macaluso, Emiliano; Mangia, Silvia; Giove, Federico
Abstract: Visuospatial attention is strongly lateralized, with the right hemisphere commonly exhibiting stronger activation and connectivity patterns than the left hemisphere during attentive processes. However, whether such asymmetry influences inter‐hemispheric information transfer and behavioral performance is not known. Here we used a region of interest (ROI) and network‐based approach to determine steady‐state fMRI functional connectivity (FC) in the whole cerebral cortex during a leftward/rightward covert visuospatial attention task. We found that the global FC topology between either ROIs or networks was independent on the attended side. The side of attention significantly modulated FC strength between brain networks, with leftward attention primarily involving the connections of the right visual network with dorsal and ventral attention networks in both the left and right hemisphere. High hemispheric functional segregation significantly correlated with faster target detection response times (i.e., better performance). Our findings suggest that the dominance of the right hemisphere in visuospatial attention is associated with an hemispheric functional segregation that is beneficial for behavioral performance. Abstract : Lateralization of spatial attention is well documented in healthy and diseased states (e.g., attention deficit disorders), but we only marginally understand the neural mechanisms underlying the relationship between functional asymmetries and behavior. We show that task performance, as measured by faster target detection response times during covert visuospatial attention, is higher when there is lower interhemispheric connectivity, that is, when the dominant right hemisphere remain functionally segregated from the left hemisphere.